2022
DOI: 10.1007/s10566-022-09705-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Body Esteem in Adolescents: psychometric properties of the Spanish version of the Body Esteem Scale (BESAA-S)

Abstract: Background “How do I perceive my own body?“ is a central question during adolescence, which addresses the subjective assessment of body image, called Body Esteem. Although concern about body esteem increases during adolescence, there is a lack of psychometrically validated measures to assess it specifically among Spanish adolescents. Objective This study aims to validate the Body-Esteem Scale for Adolescents and Adult populations (BESAA), a widely used mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 79 publications
2
15
0
Order By: Relevance
“…In fact, it indicates that the items of the questionnaire are measuring a similar concept, and the items on the scale are accurate, reliable, repeatable, and desirable. The reliability of the Spanish ( Beltrán-Garrayo et al, 2022 ), Italian ( Confalonieri et al, 2008 ), and Turkish ( Arslan et al, 2020 ) translations of this scale was also proven to be adequate. The results of all the studies identified are consistent with the findings of this study.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In fact, it indicates that the items of the questionnaire are measuring a similar concept, and the items on the scale are accurate, reliable, repeatable, and desirable. The reliability of the Spanish ( Beltrán-Garrayo et al, 2022 ), Italian ( Confalonieri et al, 2008 ), and Turkish ( Arslan et al, 2020 ) translations of this scale was also proven to be adequate. The results of all the studies identified are consistent with the findings of this study.…”
Section: Discussionmentioning
confidence: 91%
“…Overall, these findings support the validity of the body esteem scale as a measure of body esteem among 12–18-year-old Iranian adolescents. The body esteem scale developed by Mendelson has been psychometrically tested in several populations and cultures, including Spanish ( Beltrán-Garrayo et al, 2022 ), Italian ( Confalonieri et al, 2008 ), and Turkish adolescents ( Arslan et al, 2020 ), and its validity has been confirmed. In the Spanish version, like in the present study, three factors were extracted with 62.44% of the total variance ( Beltrán-Garrayo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The English version has also been adapted to different cultural contexts in urban India [ 24 ] and Singapore [ 13 ]. The BESAA has been translated into Argentinian Spanish by Forbes et al [ 22 ], but its psychometric validity was only assessed ten years later in adolescents in Spain [ 4 ]. None of the validation studies described were able to reproduce the original factor structure including all 23 items.…”
Section: Introductionmentioning
confidence: 99%